Separator, secondary battery, and electric device

CN119563256APending Publication Date: 2025-03-04CONTEMPORARY AMPEREX TECHNOLOGY CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202380049305.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-03-17
Publication Date
2025-03-04

AI Technical Summary

Technical Problem

The limited ion transmission of existing secondary batteries results in poor cycle performance, making it difficult to meet users' needs for efficient use.

Method used

Using an isolation film, by compounding the first base film and the second base film, the melting point of the second base film is lower than the first base film, the porosity ratio is in the range of 1.02≤P1/P2≤3, and the breathability is balanced and strength, improving the reliability and cycle performance of the isolation membrane.

Benefits of technology

By optimizing the air permeability and strength of the isolation film, the reliability and cycle performance of the secondary battery are improved, the battery life is extended, and the tolerance to dendrite puncture is enhanced.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119563256A_ABST
    Figure CN119563256A_ABST
Patent Text Reader

Abstract

The invention provides an isolating membrane which comprises a first base membrane and a second base membrane, and the melting point of the second base membrane is lower than that of the first base membrane; the porosity of the first base membrane is recorded as P1, the porosity of the second base membrane is recorded as P2, and P1 / P2 is greater than or equal to 1.02 and less than or equal to 3. The base film with large porosity is good in air permeability, so that the first base film with large porosity exerts excellent air permeability; the strength of the base film with small porosity is good, so that the second base film with small porosity exerts good strength and is not easily punctured by lithium dendrites. Therefore, through the cooperation of the first base membrane and the second base membrane, the isolating membrane has good air permeability and strength, so that the reliability and the cycle performance of the secondary battery can be improved.
Need to check novelty before this filing date? Find Prior Art

Description

Separator, secondary battery and electrical device Technical Field

[0001] The present application belongs to the technical field of secondary batteries, and specifically relates to an isolation membrane, a secondary battery, and an electrical device. Background Art

[0002] Secondary batteries are widely used in various consumer electronic products and electric vehicles due to their outstanding features of light weight, no pollution and no memory effect.

[0003] With the continuous development of the new energy industry, users have put forward higher requirements for the use of secondary batteries. For example, in some secondary batteries, ion transport is limited, resulting in poor battery cycle performance.

[0004] Therefore, how to make secondary batteries have better cycle performance is an urgent problem to be solved.

[0005] Summary of the Invention

[0006] In view of the technical problems existing in the background technology, the present application provides a separator, a secondary battery and an electrical device, aiming to improve the cyclability of the secondary battery.

[0007] In order to achieve the above-mentioned purpose, the first aspect of the present application provides an isolation film, which includes a first base film and a second base film, the melting point of the second base film is lower than the melting point of the first base film; the porosity of the first base film is denoted as P1, and the porosity of the second base film is denoted as P2, then 1.02≤P1 / P2≤3.

[0008] Compared with the prior art, the present application includes at least the following beneficial effects: when the melting point of the second base film is lower than the melting point of the first base film, and 1.02≤P1 / P2≤3, the air permeability and strength of the first base film and the second base film can be better balanced. Among them, the base film with a large porosity has good air permeability, and the first base film with a large porosity exerts its excellent air permeability; the base film with a small porosity has high strength, and the second base film with a small porosity exerts its good strength and is not easily punctured by dendrites. Therefore, by adopting the first base film and the second base film provided by the present application, and 1.02≤P1 / P2≤3, through the cooperation of the two layers of base film, the isolation membrane has good air permeability and strength, thereby improving the reliability and cycle performance of the secondary battery.

[0009] In any embodiment of the present application, 1.05≤P1 / P2≤2.5. When 1.05≤P1 / P2≤2.5, the air permeability and strength of the first base film and the second base film can be better balanced. This allows the separator to have good air permeability and strength, thereby improving the reliability and cycle performance of the secondary battery.

[0010] In any embodiment of the present application, the porosity of the first base film is 30%-90%, optionally 35%-85%; and / or the porosity of the second base film is 30%-70%, optionally 35%-45%.

[0011] When the porosity of the first base film is 30%-90%, and / or the porosity of the second base film is 30%-70%, the air permeability and strength of the first and second base films can be better balanced. This allows the separator to have good air permeability and strength, thereby improving the reliability and cycle performance of the secondary battery. When the porosity of the first base film is 35%-85%, and / or the porosity of the second base film is 35%-45%, the air permeability and strength of the separator can be further improved, thereby improving the reliability and cycle performance of the secondary battery.

[0012] In any embodiment of the present application, the ratio of the average pore size of the first basement membrane to the average pore size of the second basement membrane is 0.05-80, and can optionally be 0.2-40. The smaller the average pore size, the smaller the space occupied by the average pore area, the larger the space occupied by the fiber filaments of the basement membrane, and the stronger the basement membrane. Conversely, the smaller the space occupied by the fiber filaments of the basement membrane, the larger the average pore area of ​​the separator membrane and the better the air permeability. By setting the average pore size ratio within the above range, the separator membrane can be made to have both air permeability and strength, thereby improving the reliability and cycle performance of the separator membrane.

[0013] In any embodiment of the present application, the average pore size of the first base film is larger than the average pore size of the second base film. This can better meet the porosity requirements of the two base films, thereby making the separator have good air permeability and strength, thereby improving the reliability and cycle performance of the secondary battery.

[0014] In any embodiment of the present application, the average pore size of the first base film is 100 nm to 4000 nm, optionally 100 nm to 2000 nm; and / or the average pore size of the second base film is 50 nm to 2000 nm, optionally 50 nm to 500 nm. This can effectively meet the porosity requirements of both base films, thereby ensuring that the separator has good air permeability and strength, thereby improving the reliability and cycle performance of the secondary battery.

[0015] In any embodiment of the present application, the transverse tensile strength of the first base film is less than the longitudinal tensile strength of the first base film; and the ratio of the transverse tensile strength of the first base film to the longitudinal tensile strength of the first base film is 0.2-0.8, and optionally 0.3-0.6. This allows the separator to have good air permeability and strength, thereby improving the reliability and cycle performance of the secondary battery.

[0016] In any embodiment of the present application, the transverse tensile strength of the second base film is less than the longitudinal tensile strength of the second base film; optionally, the ratio of the transverse tensile strength of the second base film to the longitudinal tensile strength of the second base film is 0.45-0.9, or optionally 0.6-0.8. This allows the separator to have good air permeability and strength, thereby improving the reliability and cycle performance of the secondary battery.

[0017] In any embodiment of the present application, the transverse tensile strength of the first base film is less than that of the second base film; and / or the longitudinal tensile strength of the first base film is less than that of the second base film. This allows the separator to have good air permeability and strength, thereby improving the reliability and cycle performance of the secondary battery.

[0018] In any embodiment of the present application, the isolation film satisfies at least one of the following (1)-(4):

[0019] (1) The transverse tensile strength of the first base film is 150-900 Kgf / cm 2 , optional 200-750Kgf / cm 2 ;

[0020] (2) The longitudinal tensile strength of the first base film is 800-2500 Kgf / cm 2 , optional 1100-1900Kgf / cm 2 ;

[0021] (3) The transverse tensile strength of the second base film is 1500-3600 Kgf / cm 2 , optional 1800-3300Kgf / cm 2 ;

[0022] (4) The longitudinal tensile strength of the second base film is 1900-4000 Kgf / cm 2 , optional 2000-3500Kgf / cm 2 .

[0023] When at least one of the above (1) to (4) of the separator satisfies the given range, the separator has good air permeability and strength, thereby improving the reliability and cycle performance of the secondary battery.

[0024] In any embodiment of the present application, the ratio of the thickness of the first base film to the thickness of the second base film is greater than or equal to 1.02, and can be 1.2-3.0, so that the separator has good air permeability and strength, thereby improving the reliability and cycle performance of the secondary battery.

[0025] In any embodiment of the present application, the thickness of the first base film is 2 μm-12 μm, optionally 3 μm-6 μm; and / or the thickness of the second base film is 2 μm-12 μm, optionally 3 μm-5 μm. This allows the separator to have good air permeability and strength, thereby improving the reliability and cycle performance of the secondary battery.

[0026] In any embodiment of the present application, the ratio of the melting point of the first base film to the melting point of the second base film is greater than or equal to 1.05 and less than or equal to 3.0, and can optionally be greater than or equal to 1.1 and less than or equal to 2.5. This allows the separator to have good air permeability and strength while also taking into account heat resistance, thereby improving the reliability and cycle performance of the secondary battery.

[0027] In any embodiment of the present application, the melting point of the first base film is 160°C-360°C, optionally 180°C-350°C; and / or the melting point of the second base film is 120°C-280°C, optionally 130°C-265°C. This allows the separator to have good air permeability and strength while also taking into account heat resistance, thereby improving the reliability and cycle performance of the secondary battery.

[0028] In any embodiment of the present application, the first base film and the second base film are each independently selected from at least one of polyolefins and their derivatives, halogenated polyolefins and their derivatives, polyethers and their derivatives, polyetheretherketones and their derivatives, polyesters and their derivatives, polyimides and their derivatives, polyvinyl alcohol and their derivatives, polytetrafluoroethylene and their derivatives, polyvinyl fluoride and their derivatives, polyvinylidene fluoride and their derivatives, and polyethylene terephthalate and their derivatives. When the first base film and the second base film are respectively at least one of the above materials, the porosity of the separator can be controlled to be maintained within a suitable range, thereby improving the air permeability and strength of the separator during compounding, thereby improving the reliability and cycle performance of the secondary battery.

[0029] In any embodiment of the present application, an adhesive layer is provided between the first and second base films, and the adhesive layer includes a binder; optionally, the adhesive layer includes a binder and a filler. When an adhesive layer is provided between the first and second base films, and the adhesive layer includes a binder and a filler, the separator can have both high strength and heat resistance as well as air permeability, thereby improving the reliability and cycle performance of the secondary battery.

[0030] In any embodiment of the present application, the binder includes one or more of polyacrylate, polyacrylic acid, polytetrafluoroethylene, polyvinylidene fluoride, vinylidene fluoride-trichloroethylene copolymer, polyvinyl pyrrolidone, polyvinyl acetate, ethylene-vinyl acetate copolymer, polyethylene oxide, polyarylate, carboxymethyl cellulose, hydroxypropyl cellulose, regenerated cellulose, cellulose acetate, cellulose acetate propionate, cellulose acetate butyrate, polyacrylonitrile, polyvinyl alcohol, polyethylene, polypropylene, starch, and cyanoethyl pullulan. When an adhesive layer is provided between the first base film and the second base film, and the binder in the adhesive layer includes the above components, the separator can have high strength, heat resistance, and air permeability. The reliability and cycle performance of the secondary battery can be improved.

[0031] In any embodiment of the present application, the filler includes at least one of inorganic particles, organic particles, and an organic-metal framework material. When an adhesive layer is provided between the first base film and the second base film, and the filler in the adhesive layer includes at least one of the aforementioned inorganic particles, organic particles, and an organic-metal framework material, the filler in the adhesive layer can further improve the heat resistance and strength of the separator, thereby improving the reliability of the secondary battery.

[0032] In any embodiment of the present application, the thickness of the adhesive layer is greater than or equal to 0.3 μm, and can optionally be 0.5-2 μm. When the thickness of the adhesive layer is within the given range, the separator can have good air permeability and strength, thereby improving the reliability and cycle performance of the secondary battery.

[0033] In any embodiment of the present application, the separator has an air permeability of 200s / 100cc-400s / 100cc, optionally 250s / 100cc-320s / 100cc; and / or a porosity of 25%-80%, optionally 35%-55%. When at least one of the above characteristics of the separator falls within the given range, the separator has good air permeability and strength, thereby improving the reliability and cycle performance of the secondary battery.

[0034] A second aspect of the present application provides a method for preparing a separator, comprising: providing a first base film and a second base film, wherein the melting point of the second base film is lower than that of the first base film, and the ratio of the porosity of the first base film to the porosity of the second base film is 1.02 ≤ P1 / P2 ≤ 3; and laminating the first base film and the second base film to obtain a separator. This method can provide the separator with good air permeability and strength, thereby improving the reliability and cycle performance of the secondary battery.

[0035] In any embodiment of the present application, the preparation method further includes providing an adhesive layer slurry, the adhesive layer slurry includes a binder; setting the adhesive layer slurry on the first base film and / or the second base film to form an adhesive layer, and after compounding, the adhesive layer is located between the first base film and the second base film.

[0036] The adhesive layer slurry also includes a filler; optionally, the filler includes at least one of inorganic particles, organic particles, and an organic-metal framework material. This can provide the separator with good air permeability and strength, thereby improving the reliability and cycle performance of the secondary battery.

[0037] The third aspect of the present application provides a secondary battery comprising the separator provided in the first aspect of the present application or a separator prepared by the separator preparation method of the second aspect of the present application. When the secondary battery uses the separator, the reliability and cycle performance of the secondary battery can be improved.

[0038] In any embodiment of the present application, the secondary battery further includes a positive electrode sheet and a negative electrode sheet, with the second base film facing the negative electrode sheet. The second base film has low porosity and high strength, which can enhance resistance to dendrite puncture. Meanwhile, the first base film has excellent heat resistance and faces the positive electrode, which can improve the thermal shock resistance of the separator.

[0039] The fourth aspect of the present application provides an electric device comprising the secondary battery of the third aspect of the present application. When the secondary battery of the electric device uses the given separator, the reliability of the electric device can be improved.

[0040] Since the device of the present application includes the secondary battery provided by the present application, it has at least the same advantages as the secondary battery. BRIEF DESCRIPTION OF THE DRAWINGS

[0041] To more clearly illustrate the technical solution of this application, the following is a brief introduction to the drawings used in this application. Obviously, the drawings described below are only some embodiments of this application. For those skilled in the art, other drawings can be obtained based on the drawings without inventive effort.

[0042] FIG1 is a schematic structural diagram of an isolation membrane according to an embodiment of the present application.

[0043] FIG2 is a schematic structural diagram of an isolation membrane according to an embodiment of the present application.

[0044] FIG3 is a schematic diagram of an embodiment of a secondary battery.

[0045] FIG. 4 is an exploded view of FIG. 3 .

[0046] FIG. 5 is a schematic diagram of an embodiment of a battery module.

[0047] FIG. 6 is a schematic diagram of a battery pack according to one embodiment.

[0048] FIG. 7 is an exploded view of FIG. 6 .

[0049] FIG. 8 is a schematic diagram of an embodiment of a device using a secondary battery as a power source. DETAILED DESCRIPTION

[0050] The present application will be further described below in conjunction with specific embodiments. It should be understood that these specific embodiments are only used to illustrate the present application and are not used to limit the scope of the present application.

[0051] For the sake of clarity, only some numerical ranges are specifically disclosed herein. However, any lower limit may be combined with any upper limit to form an unspecified range; and any lower limit may be combined with other lower limits to form an unspecified range, and similarly, any upper limit may be combined with any other upper limit to form an unspecified range. In addition, each individually disclosed point or single value may itself serve as a lower limit or upper limit and be combined with any other point or single value, or with other lower limits or upper limits, to form an unspecified range.

[0052] In the description herein, unless otherwise indicated, the term "or" is inclusive. That is, the phrase "A or B" means "A, B, or both A and B." More specifically, the condition "A or B" is satisfied by any of the following conditions: A is true (or exists) and B is false (or does not exist); A is false (or does not exist) and B is true (or exists); or both A and B are true (or exist).

[0053] In the description of this article, it should be noted that, unless otherwise specified, “above” and “below” include the number itself, and “several” in “one or several” means two or more.

[0054] Unless otherwise specified, the terms used in this application have the commonly understood meanings commonly understood by those skilled in the art. Unless otherwise specified, the numerical values ​​of the various parameters mentioned in this application can be measured using various measurement methods commonly used in the art (for example, they can be tested according to the methods given in the examples of this application).

[0055] secondary batteries

[0056] A secondary battery is a battery that can be recharged to activate the active materials after discharge and continue to be used.

[0057] Typically, a secondary battery consists of a positive electrode, a negative electrode, a separator, and an electrolyte. During the battery's charge and discharge processes, active ions are inserted and removed between the positive and negative electrodes. The separator is placed between the positive and negative electrodes to provide isolation. The electrolyte conducts ions between the positive and negative electrodes.

[0058] [Isolation film]

[0059] Referring to Figure 1, an embodiment of the present application provides an isolation film 10, including a first base film 11 and a second base film 12, wherein the melting point of the second base film 12 is lower than the melting point of the first base film 11; the porosity of the first base film 11 is recorded as P1, and the porosity of the second base film 12 is recorded as P2, then 1.02≤P1 / P2≤3.

[0060] Without wishing to be limited by any theory, the inventors have found through extensive research that by selecting two base membranes with good porosity for compounding, the final isolation membrane has better air permeability and is more conducive to ion transmission. This can be preliminarily considered to be correct, but based on the current experimental results, the effect is not obvious, because good air permeability may lead to poor strength, which may be punctured, causing a short circuit between the positive and negative poles, and creating a safety hazard.

[0061] When the porosity ratio of the first base film to the second base film is 1.02≤P1 / P2≤3, the air permeability and strength of the first base film and the second base film can be better balanced, among which the base film with large porosity has good air permeability, therefore, the first base film with large porosity exerts its excellent air permeability; the base film with small porosity has good strength and is not easily punctured by dendrites, therefore, the second base film with small porosity exerts its excellent strength, so that the isolation membrane has good air permeability and strength, thereby improving the reliability and cycle performance of the secondary battery.

[0062] In any embodiment of the present application, 1.02≤P1 / P2≤3, optionally, 1.05≤P1 / P2≤2.5. P1 / P2 can be 1.02, 1.05, 1.13, 1.2, 1.3, 1.4, 1.5, 2.0, 2.3, 2.55, 3.0, or a range consisting of any two of the above values. For example, it can be 1.02-1.13, 1.05-1.2, 1.2-2.5, 1.5-2.0, 1.2-1.5, 2.0-2.5, 2.5-3.0, 1.5-2.8, etc. In this embodiment, the permeability and strength of the first base film and the second base film can be better balanced, so that the isolation membrane has good permeability and strength, thereby improving the reliability and cycle performance of the secondary battery.

[0063] In any embodiment of the present application, the porosity of the first base film is 30%-90%, optionally 35%-85%; and / or the porosity of the second base film is 30%-70%, optionally 35%-45%. For example, the porosity of the first base film can be 30%, 35%, 38%, 40%, 50%, 55%, 60%, 70%, 75%, 80%, 85%, 90%, or a range consisting of any two of the above values. For example, the porosity of the first base film can also be 30%-40%, 35%-45%, 50%-70%, 75%-80%, 80%-90%, etc. The porosity of the second base film can be 30%, 35%, 40%, 45%, 50%, 60%, 65%, 70%, or a range consisting of any two of the above values. For example, it can also be 30%-40%, 45%, 50%-60%, 65%-70%, etc.

[0064] When the porosity of the first base film is 30%-90%, and / or the porosity of the second base film is 30%-70%, the air permeability and strength of the first and second base films are better balanced. A base film with a high porosity exhibits excellent air permeability, while a base film with a low porosity exhibits superior strength, making it less susceptible to dendrite puncture. This results in a separator with excellent air permeability and strength, thereby improving the reliability and cycle performance of the secondary battery.

[0065] According to some embodiments, porosity has a well-known meaning in the art and can be tested using known equipment and methods. For example, the test can be performed with reference to GB / T 24586-2009. The test method is as follows: punch the isolation membrane or substrate into small disc samples with a diameter of 14 mm, test the thickness, and calculate the apparent volume V1 of the isolation membrane or substrate according to the cylinder volume calculation formula; refer to GB / T 24586-2009, use an inert gas such as helium or nitrogen as the medium, adopt the gas replacement method, and use a true density tester to measure the true volume V2 of the isolation membrane or substrate. Then the porosity of the isolation membrane or substrate = (V1-V2) / V1×100%. The testing instrument can be the AccuPyc II 1340 fully automatic true density tester from Micromeritics, USA.

[0066] In any embodiment of the present application, the ratio of the average pore size of the first base film to the average pore size of the second base film is 0.05-80, and can be optionally 0.2-40. The ratio of the average pore size of the first base film to the average pore size of the second base film can be 0.05, 0.1, 0.2, 0.5, 1.0, 2.0, 6.0, 9.0, 13.0, 18.0, 20.0, 25.0, 30.0, 35.0, 40.0, 45.0, 50.0, 55.0, 60.0, 70.0, 80.0, etc. Or a range consisting of any two of the above values. For example, it can also be 0.05-0.2, 0.2-1, 1-5, 5-8, 8-10, 10-14, 15-20, 20-30, 30-40, 40-60, 60-80, etc.

[0067] The smaller the average pore size, the smaller the space occupied by the average pore area, the larger the space occupied by the basement membrane fibers, and the stronger the basement membrane. Conversely, the smaller the space occupied by the basement membrane fibers, the larger the average pore area of ​​the separator membrane and the better the air permeability. By setting the average pore size ratio within the above range, the separator membrane can achieve both air permeability and strength, thereby improving the reliability and cycle performance of the separator membrane.

[0068] In any embodiment of the present application, the average pore size of the first base film is greater than the average pore size of the second base film.

[0069] In any embodiment of the present application, the average pore size of the first basement membrane is 100 nm-4000 nm, optionally 100 nm-2000 nm. For example, the average pore size of the pore structure of the first basement membrane can be 100 nm, 150 nm, 180 nm, 200 nm, 220 nm, 250 nm, 255 nm, 285 nm, 300 nm, 325 nm, 350 nm, 400 nm, 500 nm, 750 nm, 855 nm, 955 nm, 1000 nm, 1250 nm, 1350 nm, 1500 nm, 1750 nm, 1850 nm, 2000 nm, 2300 nm, 2500 nm, 2700 nm, 3000 nm, 3300 nm, 3600 nm, or 4000 nm, or a range consisting of any two of the above values. For example, it can also be 100nm-150nm, 100nm-400nm, 120nm-200nm, 200nm-250nm, 235nm-285nm, 300nm-350nm, 100nm-2000nm, 325nm-2000nm, 350nm-1850nm, 400nm-1750nm, 500nm-1500nm, 750nm-1350nm, 855nm-1250nm, 2000nm-3000nm, 3000nm-4000nm, 2500nm-3500nm, 1000-3000nm, 1000-4000nm, etc.

[0070] The average pore size of the second basement membrane is 50 nm to 2000 nm, and can be 50 nm to 500 nm. For example, the average pore size of the pore structure of the second basement membrane can be 50 nm, 75 nm, 100 nm, 120 nm, 150 nm, 180 nm, 200 nm, 225 nm, 255 nm, 300 nm, 400 nm, 500 nm, 600 nm, 700 nm, 800 nm, 1000 nm, 1250 nm, 1400 nm, 1500 nm, 1650 nm, 1800 nm, 1900 nm, or 2000 nm, or a range consisting of any two of the above values. For example, the thickness may be 50nm-100nm, 100nm-150nm, 150nm-200nm, 200nm-255nm, 250nm-300nm, 100nm-300nm, 50nm-500nm, 400nm-1900nm, 500nm-1800nm, 600nm-1650nm, 700nm-1500nm, 800nm-1400nm, 1000nm-1250nm, 1000nm-1900nm, 1000nm-2000nm, etc. The porosity requirements of the two base films can be well met, thereby making the separator have good air permeability and strength, thereby improving the reliability and cycle performance of the secondary battery.

[0071] According to some embodiments, the average pore size has a well-known meaning in the art and can be measured using methods known in the art, for example, using a mercury porosimeter with reference to GB / T 21650.1-2008.

[0072] In any embodiment of the present application, the transverse tensile strength of the first base film is less than the longitudinal tensile strength of the first base film. This configuration makes the isolation film more ductile in the transverse direction, can resist puncture by dendrites, etc., and inhibit the growth of dendrites.

[0073] In any embodiment of the present application, the ratio of the transverse tensile strength of the first base film to the longitudinal tensile strength of the first base film is 0.2-0.8, and more preferably 0.3-0.6. The ratio of the transverse tensile strength of the first base film to the longitudinal tensile strength of the first base film can be 0.2, 0.25, 0.3, 0.35, 0.4, 0.45, 0.5, 0.53, 0.62, 0.70, 0.75, 0.8, etc. Or a range consisting of any two of the above values. For example, it can also be 0.2-0.3, 0.28-0.31, 0.38-0.42, 0.32-0.36, 0.42-0.51, 0.52-0.55, 0.55-0.61, 0.62-0.7, 0.7-0.75, 0.75-0.8, etc.

[0074] Through this setting, the porosity of the first base film and the second base film can be balanced to meet 1.02≤P1 / P2≤3, and the air permeability of the isolation membrane can be guaranteed. At the same time, the strength of the isolation membrane can be increased and the ability to cope with stress deformation can be improved, so as to further improve the reliability of the battery and extend the cycle life.

[0075] In any embodiment of the present application, the transverse tensile strength of the second base film is less than the longitudinal tensile strength of the second base film. This configuration makes the isolation film more ductile in the transverse direction, can resist puncture by dendrites, etc., and inhibit the growth of dendrites.

[0076] In any embodiment of the present application, the ratio of the transverse tensile strength of the second base film to the longitudinal tensile strength of the second base film is 0.45-0.9, and more preferably 0.6-0.8. The ratio of the transverse tensile strength of the second base film to the longitudinal tensile strength of the second base film can be 0.45, 0.5, 0.53, 0.62, 0.70, 0.75, 0.8, 0.85, 0.90, etc., or a range consisting of any two of the above values. For example, it can also be 0.45-0.49, 0.49-0.53, 0.54-0.59, 0.60-0.64, 0.66-0.70, 0.72-0.75, 0.76-0.81, 0.82-0.9, etc. Through this setting, the porosity of the first base film and the second base film can be balanced to meet 1.02≤P1 / P2≤3, and the air permeability of the isolation membrane can be guaranteed. At the same time, the strength of the isolation membrane can be increased and the ability to cope with stress deformation can be improved, so as to further improve the reliability of the battery and extend the cycle life.

[0077] In any embodiment of the present application, the transverse tensile strength of the first base film is less than that of the second base film. This configuration can balance the porosity of the first and second base films to meet 1.02≤P1 / P2≤3, ensuring the air permeability of the separator, while increasing the strength of the separator and improving its ability to cope with stress and deformation, thereby further improving battery reliability and extending cycle life.

[0078] In any embodiment of the present application, the longitudinal tensile strength of the first base film is less than that of the second base film. This arrangement can balance the porosity of the first and second base films to meet 1.02≤P1 / P2≤3, ensuring the air permeability of the separator, while increasing the strength of the separator and improving its ability to cope with stress and deformation, thereby further improving the reliability of the battery and extending the cycle life.

[0079] In any embodiment of the present application, the transverse tensile strength of the first base film is 150-900 Kgf / cm 2 , optional 200-750Kgf / cm 2 For example, it can be 150Kgf / cm 2、200Kgf / cm 2 、280Kgf / cm 2 、360Kgf / cm 2 、420Kgf / cm 2 、550Kgf / cm 2 、650Kgf / cm 2 、680Kgf / cm 2 、750Kgf / cm 2 etc. Or a range consisting of any two of the above values. For example, it can also be 150-200Kgf / cm 2 、200-280Kgf / cm 2 、280-350Kgf / cm 2 、360-420Kgf / cm 2 、450-550Kgf / cm 2 、580-680Kgf / cm 2 、650-680Kgf / cm 2 、650-750Kgf / cm 2 wait.

[0080] In any embodiment of the present application, the longitudinal tensile strength of the first base film is 800-2500 Kgf / cm 2 , optional 1100-1900Kgf / cm 2 For example, it can be 800Kgf / cm 2 、880Kgf / cm 2 、960Kgf / cm 2 、1080Kgf / cm 2 、1150Kgf / cm 2 、1320Kgf / cm 2 、1550Kgf / cm 2 、1680Kgf / cm 2 、1750Kgf / cm 2 、1850Kgf / cm 2 、 1980Kgf / cm 2 、2050Kgf / cm 2 、2280Kgf / cm 2 、2500Kgf / cm 2 etc. Or a range consisting of any two of the above values. For example, it can also be 800-880Kgf / cm 2 、880-960Kgf / cm 2 、960-1080Kgf / cm 2 、1080-1150Kgf / cm2 、1150-1320Kgf / cm 2 、1320-1550Kgf / cm 2 、1550-1680Kgf / cm 2 、1750-1980Kgf / cm 2 、1950-2280Kgf / cm 2 、2250-2500Kgf / cm 2 wait.

[0081] In any embodiment of the present application, the transverse tensile strength of the second base film is 1500-3600 Kgf / cm 2 , optional 1800-3300Kgf / cm 2 For example, it can be 1500Kgf / cm 2 、1680Kgf / cm 2 、1860Kgf / cm 2 、1980Kgf / cm 2 、2150Kgf / cm 2 、2320Kgf / cm 2 、2550Kgf / cm 2 、2680Kgf / cm 2 、2750Kgf / cm 2 、2850Kgf / cm 2 、2980Kgf / cm 2 、3050Kgf / cm 2 、3280Kgf / cm 2 、3300Kgf / cm 2 etc. Or a range consisting of any two of the above values. For example, it can also be 1500-1880Kgf / cm 2 、1880-1960Kgf / cm 2 、1960-2080Kgf / cm 2 、2080-2150Kgf / cm 2 、2150-2320Kgf / cm 2 、2320-2550Kgf / cm 2 、2550-2680Kgf / cm 2 、2750-2980Kgf / cm 2 、2950-3280Kgf / cm 2 、3250-3300Kgf / cm 2 wait.

[0082] In any embodiment of the present application, the longitudinal tensile strength of the second base film is 1900-4000 Kgf / cm 2 , optional 2000-3500Kgf / cm 2 For example, it can be 1900Kgf / cm 2 、1980Kgf / cm 2 、2060Kgf / cm 2 、2180Kgf / cm 2 、2250Kgf / cm 2 、2320Kgf / cm 2 、2550Kgf / cm 2 、2680Kgf / cm 2 、2750Kgf / cm 2 、2850Kgf / cm 2 、2980Kgf / cm 2 、3050Kgf / cm 2 、3280Kgf / cm 2 、3300Kgf / cm 2 、3550Kgf / cm 2 、3780Kgf / cm 2 、4000Kgf / cm 2 etc. Or a range consisting of any two of the above values. For example, it can also be 1900-1980Kgf / cm 2 、1980-2060Kgf / cm 2 、1960-2080Kgf / cm 2 、2080-2150Kgf / cm 2 、2150-2320Kgf / cm 2 、2320-2550Kgf / cm 2 、2550-2680Kgf / cm 2 、2750-2980Kgf / cm 2 、2950-3280Kgf / cm 2 、3250-3300Kgf / cm 2 、3150-3380Kgf / cm 2 、3450-3680Kgf / cm 2 、3850-4000Kgf / cm 2 This arrangement can balance the porosity of the first and second base films to meet the requirement of 1.02≤P1 / P2≤3, ensuring the air permeability of the separator. Furthermore, it can increase the strength of the separator and enhance its ability to cope with stress and deformation, thereby further improving the reliability of the battery and extending its cycle life.

[0083] The transverse tensile strength (MD) and longitudinal tensile strength (TD) of the separator or base film have well-known meanings in the art and can be measured using methods known in the art. For example, both can be tested in accordance with standard GB / T 36363-2018.

[0084] In any embodiment of the present application, the thickness of the first base film is 2 μm-12 μm, and can be 3 μm-6 μm. For example, it can be 2 μm, 2.5 μm, 2.6 μm, 5 μm, 7 μm, 9 μm, 10 μm, 12 μm, or a range consisting of any two of the above values. For example, it can also be 1 μm-2.5 μm, 2 μm-2.6 μm, 3 μm-6 μm, 5 μm-9 μm, 10 μm-12 μm, etc.

[0085] In some embodiments, the thickness of the second base film is 2 μm-12 μm, and may be 3 μm-5 μm. For example, the thickness may be 2 μm, 3 μm, 3.5 μm, 5 μm, 9 μm, 10 μm, 12 μm, or a range consisting of any two of the above values. For example, the thickness may be 2 μm-3.5 μm, 3 μm-5 μm, 5 μm-6 μm, 9 μm-12 μm, etc.

[0086] When the thickness of the first base film and the thickness of the second base film are 2μm-12μm, the permeability and strength of the base film can be balanced. On the premise that the permeability and strength of the diaphragm meet the requirements, the thickness of the diaphragm can be made easier to meet the battery energy density requirements.

[0087] According to some embodiments, thickness has a well-known meaning in the art and can be measured using methods known in the art. For example, six sets of parallel samples are taken and the thickness of each set of samples is measured at different locations using a micrometer thickness gauge. At least 20 points are measured for each set of samples, and the average thickness of the six sets of samples is taken as the base film thickness.

[0088] In any embodiment of the present application, the ratio of the melting point of the first base film to the melting point of the second base film is greater than or equal to 1.05 and less than or equal to 3.0, and can optionally be greater than or equal to 1.1 and less than or equal to 2.5. For example, the ratio of the melting point of the first base film to the melting point of the second base film in degrees Celsius can be 1.05, 1.1, 1.2, 1.3, 1.35, 1.5, 1.6, 1.75, 1.95, 2.0, 2.2, 2.5, 2.6, 2.7, 2.9, 3.0, or a range consisting of any two of the above values. For example, it can also be 1.05-1.2, 1.2-1.4, 1.35-1.5, 1.5-1.65, 1.6-1.75, 1.1-2.0, 1.1-2.5, 1.95-2.1, 2.2-2.5, 2.5-3.0, etc. In some embodiments, a ratio of the melting point in degrees Celsius of the first base film to the melting point in degrees Celsius of the second base film may be 1.1-2.5.

[0089] When the ratio of the melting point of the first base film to the melting point of the second base film is greater than or equal to 1.05 and less than or equal to 3.0, the first base film with a higher melting point primarily contributes to its heat resistance, or in other words, the base film with a higher porosity has a higher melting point and better heat resistance, while the second base film with a lower porosity primarily contributes to its strength. Therefore, the combination of the two can result in a separator with both high strength and heat resistance. When the ratio of the melting point of the first base film to the melting point of the second base film is selected to be greater than or equal to 1.1 and less than or equal to 2.5, the strength and heat resistance of the separator can be further improved.

[0090] In any embodiment of the present application, the melting point of the first base film is 160°C-360°C, for example, 160°C, 165°C, 170°C, 180°C, 196°C, 200°C, 235°C, 245°C, 260°C, 280°C, 290°C, 300°C, 315°C, 320°C, 330°C, 340°C, 350°C, 360°C, or a range consisting of any two of the above values. For example, it can also be 160°C-170°C, 180°C-235°C, 180°C-350°C, 225°C-280°C, 290°C-315°C, 300°C-360°C, etc. In some embodiments, the melting point of the first base film can be 180°C-350°C. The melting point of the second base film is 120°C-280°C, for example, 120°C, 130°C, 135°C, 140°C, 150°C, 155°C, 180°C, 200°C, 230°C, 265°C, 280°C, or a range consisting of any two of the above values. For example, it can also be 120°C-135°C, 130°C-150°C, 135°C-150°C, 145°C-155°C, 150°C-250°C, 250°C-280°C, 300°C-265°C, 120°C-280°C, etc. In some embodiments, the melting point of the second base film can be 130°C-265°C. It can be 130°C-265°C.

[0091] When the melting point of the first base film is 160°C-360°C, and / or the melting point of the second base film is 120°C-280°C, the melting point of the first base film is higher than that of the second base film. The first base film with a high melting point primarily contributes to its heat resistance, while the second base film with high strength primarily contributes to its strength. Therefore, the combination of the two can provide a separator with both high strength and heat resistance. When the melting point of the first base film is selected to be 180°C-350°C, and / or the melting point of the second base film is selected to be 130°C-265°C, the strength and heat resistance of the separator can be further improved.

[0092] According to some embodiments, the melting point has a meaning generally known in the art and can be determined using methods known in the art. For example, it can be determined using differential scanning calorimetry. For details, reference may be made to the standard GB / T 19466.3-2004. As an example, the determination can be performed as follows: 4-6 mg of the sample to be tested is placed in the sample chamber of a differential scanning calorimeter. The temperature is raised from 25°C to 400°C at a rate of 10°C / min. A melting endothermic curve of the sample is obtained, and the temperature corresponding to the peak of the curve is the melting point of the sample.

[0093] The present inventors have found through in-depth research that when the separator of the present application satisfies the above conditions and optionally satisfies one or more of the following conditions, the performance of the secondary battery can be further improved.

[0094] There is no particular restriction on the materials of the first base film and the second base film, and any known base film with good chemical stability and strength stability can be selected. The materials of the first base film and the second base film of the isolation film are the same or different.

[0095] In any embodiment of the present application, the first base film and the second base film are each independently selected from at least one of polyolefins and their derivatives, halogenated polyolefins and their derivatives, polyethers and their derivatives, polyetheretherketones and their derivatives, polyesters and their derivatives, polyimides and their derivatives, polyvinyl alcohols and their derivatives, polytetrafluoroethylenes and their derivatives, polyvinyl fluoride and their derivatives, polyvinylidene fluoride and their derivatives, polyethylene terephthalate and their derivatives. Derivatives generally refer to products derived from the replacement of hydrogen atoms or atomic groups in a compound by other atoms or atomic groups. When the first base film and the second base film are respectively at least one of the above materials, the porosity of the isolation film can be controlled to be maintained in a suitable range, so that the air permeability and strength of the isolation film during compounding are improved, thereby improving the reliability and cycle performance of the secondary battery.

[0096] Referring to Figure 1, an embodiment of the present application provides an isolation film 10, including a first base film 11 and a second base film 12. In any embodiment of the present application, an adhesive layer 13 is further provided between the first base film 11 and the second base film 12, and the adhesive layer includes a binder; optionally, the adhesive layer includes a binder and a filler. When an adhesive layer is provided between the first base film and the second base film, when an adhesive layer is provided between the first base film and the second base film, it can not only compensate for the process defects in the hot pressing composite process of the base film, but also further improve the physical properties of the isolation film (such as tensile strength, puncture strength, heat resistance, etc.), thereby improving the reliability of the secondary battery. The filler is located between the first base film and the second base film, which can also avoid the problem of powder loss.

[0097] The first base film and the second base film can be directly laminated by hot pressing. During the hot pressing process, if the temperature is too high, the porosity will be small and the air permeability will be poor; if the temperature is too low, the first base film and the second base film will not be firmly bonded. Therefore, it is necessary to adjust the hot pressing temperature appropriately. Optionally, the hot pressing temperature is 20°C-50°C.

[0098] In any embodiment of the present application, the binder includes one or more of polyacrylate, polyacrylic acid, polytetrafluoroethylene, polyvinylidene fluoride, vinylidene fluoride-trichloroethylene copolymer, polyvinyl pyrrolidone, polyvinyl acetate, ethylene-vinyl acetate copolymer, polyethylene oxide, polyarylate, carboxymethyl cellulose, hydroxypropyl cellulose, regenerated cellulose, cellulose acetate, cellulose acetate propionate, cellulose acetate butyrate, polyacrylonitrile, polyvinyl alcohol, polyethylene, polypropylene, starch, and cyanoethyl pullulan. When an adhesive layer is provided between the first base film and the second base film, and the binder in the adhesive layer includes the above components, the separator can have high strength, heat resistance, and air permeability. The reliability and cycle performance of the secondary battery can be improved.

[0099] In any embodiment of the present application, the filler includes at least one of inorganic particles, organic particles, and organic-metal framework materials.

[0100] Optionally, the inorganic particles include one or more of inorganic particles having a dielectric constant of 5 or greater, inorganic particles having ion conductivity but not storing ions, and inorganic particles capable of undergoing electrochemical reactions.

[0101] Alternatively, the inorganic particles having a dielectric constant of 5 or more may include boehmite, aluminum oxide, zinc oxide, silicon oxide, titanium oxide, zirconium oxide, barium oxide, calcium oxide, magnesium oxide, nickel oxide, tin oxide, cerium oxide, yttrium oxide, hafnium oxide, aluminum hydroxide, magnesium hydroxide, silicon carbide, boron carbide, aluminum nitride, silicon nitride, boron nitride, magnesium fluoride, calcium fluoride, barium fluoride, barium sulfate, magnesium aluminum silicate, lithium magnesium silicate, sodium magnesium silicate, bentonite, hectorite, zirconium titanate, barium titanate, Pb(Zr,Ti)O3 (abbreviated as PZT), Pb 1-m La m Zr 1-n Ti n O3 (abbreviated as PLZT, 0<m<1, 0<n<1), Pb(Mg3Nb 2 / 3 )O3-PbTiO3 (abbreviated as PMN-PT), and at least one of their respective modified inorganic particles. Optionally, the modification method of each inorganic particle may be chemical modification and / or physical modification. The chemical modification method includes coupling agent modification (for example, using silane coupling agent, titanate coupling agent, etc.), surfactant modification, polymer grafting modification, etc. The physical modification method may be mechanical force dispersion, ultrasonic dispersion, high energy treatment, etc. The modification treatment can reduce the agglomeration of inorganic particles, thereby enabling the adhesive layer to have a more stable and uniform structure; in addition, by selecting a coupling agent, surfactant or polymer with a specific functional group to modify the inorganic particles, it is also helpful to improve the adhesive layer's wetting and retention properties for the electrolyte, and improve the adhesiveness of the adhesive layer to the first base film and the second base film.

[0102] Alternatively, the inorganic particles having ion conductivity but not storing ions may include Li3PO4, lithium titanium phosphate Li x1 Ti y1 (PO4)3, lithium aluminum titanium phosphate Li x2 Al y2 Ti z1 (PO4)3, (LiAlTiP) x3 O y3 Type glass, lanthanum lithium titanate Li x4 La y4 TiO3, lithium germanium thiophosphate Li x5 Ge y5 P z2 S w , lithium nitride Li x6 N y6 、SiS2 type glass Li x7 Si y7 S z3 and P2S5 glass Li x8 P y8 S z4 At least one of the following: 0<x1<2, 0<y1<3, 0<x2<2, 0<y2<1, 0<z1<3, 0<x3<4, 0<y3<13, 0<x4<2, 0<y4<3, 0<x5<4, 0<y5<1, 0<z2<1, 0<w<5, 0<x6<4, 0<y6<2, 0<x7<3, 0<y7<2, 0<z3<4, 0<x8<3, 0<y8<3, 0<z4<7. This can further improve the ion conductivity of the isolation membrane.

[0103] Alternatively, the inorganic particles capable of undergoing electrochemical reaction may include at least one of lithium-containing transition metal oxides, lithium-containing phosphates, carbon-based materials, silicon-based materials, tin-based materials, and lithium-titanium compounds.

[0104] Alternatively, the organic particles may include one or more of polycarbonate, polythiophene, polypyridine, polystyrene, polyacrylic wax, polyethylene, polypropylene, cellulose, a cellulose modifier (e.g., carboxymethyl cellulose), a melamine resin, a phenolic resin, a polyester (e.g., polyethylene terephthalate, polyethylene naphthalate, polybutylene terephthalate), a silicone resin, a polyimide, a polyamideimide, a polyaromatic amide, polyphenylene sulfide, a polysulfone, a polyethersulfone, a polyetheretherketone, a polyaryletherketone, a copolymer of butyl acrylate and ethyl methacrylate (e.g., a cross-linked polymer of butyl acrylate and ethyl methacrylate).

[0105] Optionally, the organic-metal framework material may include one or more of a nitrogen-containing heterocyclic ligand building structure, an organic carboxylic acid ligand building structure, and a nitrogen-oxygen mixed ligand building structure.

[0106] In some embodiments, the content of the binder may be greater than or equal to 10%, optionally 10%-30%, based on the total weight of the adhesive layer.

[0107] In some embodiments, the content of the filler may be less than or equal to 90%, optionally 40%-90%, 60%-80%, based on the total weight of the adhesive layer.

[0108] In some embodiments, the bonding layer may further include a dispersant, such as carboxymethyl cellulose, to adjust the viscosity of the bonding layer slurry and improve the quality and uniformity of the bonding layer.

[0109] In some embodiments, the content of the dispersant may be less than or equal to 25%, optionally less than or equal to 20%, based on the total weight of the adhesive layer.

[0110] When an adhesive layer is provided between the first base film and the second base film, and the filler in the adhesive layer includes at least one of the above-mentioned inorganic particles, organic particles, and organic-metal framework materials, the filler in the adhesive layer can further improve the heat resistance and strength of the isolation membrane, thereby improving the reliability of the secondary battery.

[0111] In any embodiment of the present application, the thickness of the adhesive layer is greater than or equal to 0.3 μm, and can be optionally 0.5-2 μm. When the thickness of the adhesive layer is within the given range, the reliability of the secondary battery can be improved.

[0112] In any embodiment of the present application, the separator has an air permeability of 200s / 100cc-400s / 100cc, optionally 250s / 100cc-320s / 100cc; and / or a porosity of 25%-80%. When at least one of the above characteristics of the separator falls within the given range, the separator has good air permeability and strength, thereby improving the reliability and cycle performance of the secondary battery.

[0113] In any embodiment of the present application, a method for preparing a separator includes providing a first base film and a second base film, wherein the melting point of the second base film is lower than that of the first base film, and the ratio of the porosity of the first base film to the porosity of the second base film is 1.02 ≤ P1 / P2 ≤ 3; and laminating the first base film and the second base film to obtain a separator. This can provide the separator with good air permeability and strength, thereby improving the reliability and cycle performance of the secondary battery.

[0114] In any embodiment of the present application, the preparation method further includes providing an adhesive layer slurry, the adhesive layer slurry includes a binder; setting the adhesive layer slurry on the first base film and / or the second base film to form an adhesive layer, and after compounding, the adhesive layer is located between the first base film and the second base film.

[0115] The adhesive layer slurry also includes a filler; optionally, the filler includes at least one of inorganic particles, organic particles, and an organic-metal framework material. This can provide the separator with good air permeability and strength, thereby improving the reliability and cycle performance of the secondary battery.

[0116] In any embodiment of the present application, an adhesive layer slurry is prepared, the adhesive layer slurry including a binder, and the adhesive layer slurry is applied to the first base film and / or the second base film before lamination. Optionally, the adhesive layer slurry includes a binder and a filler. When the adhesive layer slurry is applied to the first base film and / or the second base film before lamination, and the adhesive layer slurry includes the above components, the reliability of the secondary battery can be improved.

[0117] Unless otherwise specified, all raw materials used in the separator (eg, the first base film, the second base film, the adhesive, the filler, etc.) can be purchased commercially.

[0118] In any embodiment of the present application, a secondary battery includes a positive electrode sheet, a negative electrode sheet, and a separator provided by any of the above embodiments of the present application, or a separator prepared by the separator preparation method of any of the above embodiments, wherein the separator is disposed between the positive electrode sheet and the negative electrode sheet. When the secondary battery uses the given separator, the reliability and cycle performance of the secondary battery can be improved.

[0119] In any embodiment of the present application, the second base film of the separator faces the negative electrode. The first base film has good heat resistance and faces the positive electrode, while the second base film has high strength and faces the negative electrode, which can increase the resistance to lithium dendrite puncture and improve the reliability of the secondary battery.

[0120] In any embodiment of the present application, an electrical device includes the secondary battery of any of the above embodiments of the present application. When the secondary battery of the electrical device uses the given separator, the reliability of the electrical device can be improved.

[0121] Since the device of the present application includes the secondary battery provided by the present application, it has at least the same advantages as the secondary battery.

[0122] [Positive electrode]

[0123] In a secondary battery, the positive electrode sheet generally includes a positive electrode current collector and a positive electrode film layer disposed on the positive electrode current collector, wherein the positive electrode film layer includes a positive electrode active material.

[0124] The positive electrode current collector may be a conventional metal foil or a composite current collector (a metal material may be disposed on a polymer substrate to form a composite current collector). As an example, the positive electrode current collector may be an aluminum foil.

[0125] The specific type of the positive electrode active material is not limited, and any active material known in the art that can be used for the positive electrode of a secondary battery can be used. Those skilled in the art can select it according to actual needs.

[0126] As an example, the positive electrode active material may include, but is not limited to, one or more of lithium transition metal oxides, olivine-structured lithium-containing phosphates, and their respective modified compounds. Examples of lithium transition metal oxides may include, but are not limited to, one or more of lithium cobalt oxide, lithium nickel oxide, lithium manganese oxide, lithium nickel cobalt oxide, lithium manganese cobalt oxide, lithium nickel manganese oxide, lithium nickel cobalt manganese oxide, lithium nickel cobalt aluminum oxide, and their modified compounds. Examples of olivine-structured lithium-containing phosphates may include, but are not limited to, one or more of lithium iron phosphate, a composite material of lithium iron phosphate and carbon, lithium manganese phosphate, a composite material of lithium manganese phosphate and carbon, lithium manganese iron phosphate, a composite material of lithium manganese iron phosphate and carbon, and their modified compounds. These materials can all be obtained through commercial channels.

[0127] The modified compounds of the above materials may be doping-modified and / or surface-coated modified materials.

[0128] The positive electrode film layer usually optionally includes a binder, a conductive agent and other optional additives.

[0129] As an example, the conductive agent may be one or more of superconducting carbon, acetylene black, carbon black, Ketjen black, carbon dots, carbon nanotubes, conductive carbon black (Super P, SP), graphene, and carbon nanofibers.

[0130] As an example, the binder can be one or more of styrene butadiene rubber (SBR), water-based acrylic resin, polyvinylidene difluoride (PVDF), polytetrafluoroethylene (PTFE), ethylene-vinyl acetate copolymer (EVA), polyacrylic acid (PAA), carboxymethyl cellulose (CMC), polyvinyl alcohol (PVA) and polyvinyl butyral (PVB).

[0131] [Negative electrode]

[0132] In a secondary battery, the negative electrode plate generally includes a negative electrode current collector and a negative electrode film layer disposed on the negative electrode current collector, wherein the negative electrode film layer includes a negative electrode active material.

[0133] The negative electrode current collector may be a conventional metal foil or a composite current collector (for example, a metal material may be disposed on a polymer substrate to form a composite current collector). As an example, the negative electrode current collector may be a copper foil.

[0134] The specific type of the negative electrode active material is not limited, and active materials that can be used for the negative electrode of a secondary battery known in the art can be used, and those skilled in the art can make a selection according to actual needs. As an example, the negative electrode active material may include, but is not limited to, one or more of artificial graphite, natural graphite, hard carbon, soft carbon, silicon-based materials and tin-based materials. The silicon-based material may be selected from one or more of elemental silicon, silicon oxide compounds (such as silicon monoxide), silicon-carbon composites, silicon-nitrogen composites, and silicon alloys. The tin-based material may be selected from one or more of elemental tin, tin oxide compounds, and tin alloys. These materials can all be obtained commercially.

[0135] In some embodiments, to further improve the energy density of the battery, the negative electrode active material may include a silicon-based material.

[0136] The negative electrode film layer usually optionally includes a binder, a conductive agent and other optional additives.

[0137] As an example, the conductive agent may be one or more of superconducting carbon, acetylene black, carbon black, Ketjen black, carbon dots, carbon nanotubes, graphene, and carbon nanofibers.

[0138] As an example, the binder may be one or more of styrene-butadiene rubber (SBR), water-based acrylic resin, polyvinylidene fluoride (PVDF), polytetrafluoroethylene (PTFE), ethylene-vinyl acetate copolymer (EVA), polyvinyl alcohol (PVA) and polyvinyl butyral (PVB).

[0139] As an example, other optional auxiliary agents may be thickening and dispersing agents (such as carboxymethylcellulose sodium, CMC-Na), and PTC thermistor materials.

[0140] [Electrolyte]

[0141] A secondary battery may include an electrolyte that conducts ions between a positive electrode and a negative electrode. The electrolyte may include an electrolyte salt and a solvent.

[0142] As an example, the electrolyte salt can be selected from one or more of lithium hexafluorophosphate (LiPF6), lithium tetrafluoroborate (LiBF4), lithium perchlorate (LiClO4), lithium hexafluoroarsenate (LiAsF6), lithium bis(fluorosulfonyl)imide (LiFSI), lithium bis(trifluoromethanesulfonyl)imide (LiTFSI), lithium trifluoromethanesulfonate (LiTFS), lithium difluorooxalatoborate (LiDFOB), lithium dioxalatoborate (LiBOB), lithium difluorophosphate (LiPO2F2), lithium difluorobis(oxalatophosphate) (LiDFOP) and lithium tetrafluorooxalatophosphate (LiTFOP).

[0143] As an example, the solvent may be selected from ethylene carbonate (EC), propylene carbonate (PC), methyl ethyl carbonate (EMC), diethyl carbonate (DEC), dimethyl carbonate (DMC), dipropyl carbonate (DPC), methyl propyl carbonate (MPC), ethyl propyl carbonate (EPC), butylene carbonate (BC), fluoroethylene carbonate (FEC), methyl formate (MF), methyl acetate (MA), ethyl acetate (EA), n-propyl acetate (PA), methyl propionate (MP), ethyl propionate (EP), n-propyl propionate (n-propyl propionate) One or more of the group consisting of propionate (PP), methyl butyrate (Methyl Butyrate MB), ethyl butyrate (Ethyl Butyrate, EB), 1,4-butyrolactone (1,4-Butyrolactone, GBL), tetramethylene sulfone (SF), dimethyl sulfone (Methyl Sulfone, MSM), methyl ethyl sulfone (Methyl Ethyl Sulfone, EMS) and diethyl sulfone (Diethyl Sulfone, ESE).

[0144] In some embodiments, the electrolyte further includes additives. For example, the additives may include negative electrode film-forming additives, positive electrode film-forming additives, or additives capable of improving certain battery properties, such as additives that improve battery overcharge performance, additives that improve battery high-temperature performance, and additives that improve battery low-temperature performance.

[0145] In some embodiments, the secondary battery may be a lithium ion secondary battery. In any embodiment of the present application, the second base film of the separator faces the negative electrode.

[0146] When the porosity of the first base membrane is greater than the porosity of the second base membrane, the air permeability and strength of the first base membrane and the second base membrane can complement each other better, wherein the base membrane with large porosity has good air permeability, therefore, the first base membrane with large porosity exerts its excellent air permeability; the base membrane with small porosity has good strength and is not easily punctured by lithium dendrites, so that the isolation membrane has good air permeability and strength, thereby improving the reliability of the secondary battery.

[0147] The embodiment of the present application has no particular limitation on the shape of the secondary battery, which can be cylindrical, square, or any other shape. FIG3 shows a secondary battery 5 with a square structure as an example.

[0148] In some embodiments, the secondary battery may include an outer package for encapsulating a positive electrode sheet, a negative electrode sheet, and an electrolyte, wherein the second base film of the separator faces the negative electrode sheet.

[0149] In some embodiments, the outer packaging of the secondary battery can be a hard shell, such as a hard plastic shell, an aluminum shell, or a steel shell. The outer packaging of the secondary battery can also be a soft package, such as a bag-type soft package. The material of the soft package can be plastic, such as one or more of polypropylene (PP), polybutylene terephthalate (PBT), and polybutylene succinate (PBS).

[0150] In some embodiments, referring to FIG4 , the outer packaging may include a housing 51 and a cover 53. The housing 51 may include a bottom plate and side plates connected to the bottom plate, which together form a receiving cavity. The housing 51 may have an opening communicating with the receiving cavity, and the cover 53 may be positioned over the opening to seal the receiving cavity.

[0151] The preparation method of the secondary battery of the present application is well known. In some embodiments, the positive electrode sheet, the separator, the negative electrode sheet and the electrolyte can be assembled to form a secondary battery. As an example, the positive electrode sheet, the separator, and the negative electrode sheet can be formed into an electrode assembly through a winding process and / or a lamination process, and the electrode assembly is placed in an outer package, dried and injected with electrolyte, and then vacuum packaged, left to stand, formed, and shaped to obtain a battery cell. Multiple battery cells can also be further connected in series, in parallel, or mixed to form a battery module. Multiple battery modules can also be connected in series, in parallel, or mixed to form a battery pack. In some embodiments, multiple battery cells can also directly form a battery pack.

[0152] Figure 5 shows an example battery module 4. Referring to Figure 5 , within the battery module 4, multiple secondary batteries 5 may be arranged sequentially along the length of the battery module 4. Of course, any other arrangement is also possible. Furthermore, the multiple secondary batteries 5 may be secured together using fasteners.

[0153] The battery module 4 may further include a housing having a housing space, and the plurality of secondary batteries 5 may be housed in the housing space.

[0154] In some embodiments, the battery modules described above may also be assembled into a battery pack, and the number of battery modules contained in the battery pack may be adjusted according to the application and capacity of the battery pack.

[0155] Figures 6 and 7 illustrate an example battery pack 1. Referring to Figures 6 and 7 , the battery pack 1 may include a battery box and multiple battery modules 4 disposed within the battery box. The battery box comprises an upper case 2 and a lower case 3. The upper case 2 can be positioned over the lower case 3 to form an enclosed space for accommodating the battery modules 4. The multiple battery modules 4 can be arranged in any manner within the battery box.

[0156] [Installation]

[0157] The present application also provides an electrical device, which includes the secondary battery of the present application. The battery cell, battery module, or battery pack can serve as a power source for the device, or as an energy storage unit for the device. The device can be, but is not limited to, a mobile device (e.g., a mobile phone, a laptop computer), an electric vehicle (e.g., a pure electric vehicle, a hybrid electric vehicle, a plug-in hybrid electric vehicle, an electric bicycle, an electric scooter, an electric golf cart, an electric truck), an electric train, a ship, a satellite, or an energy storage system.

[0158] The device can select a battery cell, a battery module or a battery pack according to its usage requirements.

[0159] Figure 8 shows an example of an electric device. This device can be a pure electric vehicle, a hybrid electric vehicle, or a plug-in hybrid electric vehicle. To meet the high power and high energy density requirements of the secondary battery, a battery pack or battery module can be used.

[0160] As another example, an electric device may be a mobile phone, a tablet computer, or a laptop computer. Such an electric device is generally required to be lightweight and thin, and may use a battery cell as a power source.

[0161] Since the device of the present application includes the secondary battery provided by the present application, it has at least the same advantages as the secondary battery.

[0162] The beneficial effects of the present application are further illustrated below with reference to the examples.

[0163] In order to make the technical problems, technical solutions and beneficial effects solved by the embodiments of the present application clearer, the following will be further described in detail with reference to the embodiments and drawings. Obviously, the described embodiments are only a part of the embodiments of the present application, rather than all the embodiments. The following description of at least one exemplary embodiment is actually only illustrative and is in no way intended to limit the present application and its applications. Based on the embodiments in this application, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of this application.

[0164] 1. Preparation of isolation membrane

[0165] Isolation film 1:

[0166] (1) Providing a first base film and a second base film: the material of the first base film includes polypropylene (PP), and the material of the second base film includes polyethylene (PE); wherein the porosity ratio of the first base film and the second base film is controlled within a target range.

[0167] (2) Preparation of bonding layer slurry: boehmite, polyacrylate, and carboxymethyl cellulose were mixed evenly in a proper amount of deionized water as a solvent in a ratio of 4:1:1 to prepare bonding layer slurry.

[0168] (3) The adhesive layer slurry described in step (2) is applied to at least one side of the first base film and the second base film described in step (1) to form a bonding layer.

[0169] The preparation method of the isolation membrane of Examples 2-11 is similar to the preparation method of the isolation membrane in Example 1, except that the material or porosity of the base membrane is adjusted.

[0170] The isolation film 1-11 also satisfies the following conditions: the transverse tensile strength of the first base film is less than the longitudinal tensile strength of the first base film; the ratio of the transverse tensile strength of the first base film to the longitudinal tensile strength of the first base film is 0.2-0.8. The transverse tensile strength of the second base film is less than the longitudinal tensile strength of the second base film; the ratio of the transverse tensile strength of the second base film to the longitudinal tensile strength of the second base film is 0.45-0.9. The transverse tensile strength of the first base film is less than the transverse tensile strength of the second base film; the longitudinal tensile strength of the first base film is less than the longitudinal tensile strength of the second base film. Among them, the transverse tensile strength of the first base film in Example 1 is 600Kgf / cm 2 , the longitudinal tensile strength of the first base film is 1250Kgf / cm 2 ; The transverse tensile strength of the second base film is 1350Kgf / cm 2 The longitudinal tensile strength of the second base film is 1700Kgf / cm 2 ; The transverse tensile strength of the isolation film is 1650Kgf / cm2 The longitudinal tensile strength of the isolation film is 2700Kgf / cm 2 The transverse tensile strength of the first base film in Example 6 is 550 Kgf / cm 2 , the longitudinal tensile strength of the first base film is 700Kgf / cm 2 ; The transverse tensile strength of the second base film is 650Kgf / cm 2 The longitudinal tensile strength of the second base film is 1300Kgf / cm 2 ; The transverse tensile strength of the isolation film is 800Kgf / cm 2 , the longitudinal tensile strength of the isolation film is 2000Kgf / cm 2 The transverse tensile strength of the first base film in Example 9 is 550 Kgf / cm 2 , the longitudinal tensile strength of the first base film is 700Kgf / cm 2 ; The transverse tensile strength of the second base film is 1450Kgf / cm 2 The longitudinal tensile strength of the second base film is 1850Kgf / cm 2 ; The transverse tensile strength of the isolation film is 1500Kgf / cm 2 , the longitudinal tensile strength of the isolation film is 2500Kgf / cm 2 .

[0171] The isolation membrane prepared by the above method was subjected to relevant performance tests, and the specific results are shown in Table 1.

[0172] 2. Preparation of batteries

[0173] Example 1

[0174] 1. Preparation of positive electrode sheet

[0175] The positive electrode active material LiNi 0.8 Co 0.1 Mn 0.1 O2 (NCM811), conductive agent carbon black (SuperP), and binder polyvinylidene fluoride (PVDF) are mixed uniformly in an appropriate amount of solvent N-methylpyrrolidone (NMP) at a mass ratio of 96.2:2.7:1.1 to obtain a positive electrode slurry. The positive electrode slurry is coated on the positive electrode current collector aluminum foil, and the positive electrode sheet is obtained through drying, cold pressing, slitting, and cutting processes. The positive electrode surface density is 0.207 mg / mm 2 , compacted density is 3.5g / cm 3 .

[0176] 2. Preparation of negative electrode sheet

[0177] The negative electrode active material artificial graphite, conductive agent carbon black (SuperP), binder styrene-butadiene rubber (SBR) and sodium carboxymethyl cellulose (CMC-Na) were mixed uniformly in a suitable amount of deionized water as a solvent at a mass ratio of 96.4:0.7:1.8:1.1 to obtain a negative electrode slurry. The negative electrode slurry was coated on the negative electrode current collector copper foil. After drying, cold pressing, slitting and cutting, the negative electrode sheet was obtained. The negative electrode surface density is 0.126 mg / mm 2 , compacted density is 1.7g / cm 3 .

[0178] 3. Isolation film

[0179] The isolation film used was the isolation film 1 prepared above.

[0180] 4. Preparation of electrolyte

[0181] Ethylene carbonate (EC) and ethyl methyl carbonate (EMC) are mixed in a mass ratio of 30:70 to obtain an organic solvent. Fully dried electrolyte salt LiPF6 is dissolved in the above mixed solvent. The concentration of the electrolyte salt is 1.0 mol / L. After mixing evenly, an electrolyte solution is obtained.

[0182] 5. Preparation of secondary batteries

[0183] The positive electrode sheet, the separator, and the negative electrode sheet are stacked in order, with the separator placed between the positive electrode sheet and the negative electrode sheet to serve as an isolation, and then wound to obtain an electrode assembly; the electrode assembly is placed in an outer package, and the prepared electrolyte is injected into the dried secondary battery. After vacuum packaging, standing, formation, and shaping processes, a secondary battery is obtained.

[0184] The preparation methods of the secondary batteries of Examples 2-11 and Comparative Examples 1-3 are similar to that of the secondary battery of Example 1, except that different isolation membranes are used (Examples 1-11 use isolation membranes 1-11, and Comparative Examples 1-3 use isolation membranes 11 and 14). See Table 1 for details.

[0185] Unless otherwise specified, all raw materials used in the separator (eg, the first base film, the second base film, the adhesive, the filler, etc.) can be purchased commercially.

[0186] 3. Battery performance test

[0187] 1. 250℃ thermal shrinkage test

[0188] The method for testing the thermal shrinkage of the isolation film is as follows:

[0189] (1) Sample preparation: Use a punch to punch out samples with a width of 50 mm and a length of 100 mm. 5-10 parallel samples are placed on a glass plate and fixed on all four sides with paper clips. (2) Test: Set the temperature of the forced draft oven to a specified temperature, for example, 250°C. After the temperature reaches the set temperature and stabilizes for 60 minutes, place the glass plate in the oven, time it for 1 hour, and measure the length of the diaphragm. The values ​​are marked as a. (3) Calculation: Lengthwise shrinkage A = (100-a) / 100*100%; record the value of A and take the average of the five values.

[0190] 2. Battery cycle performance test

[0191] The full-cell capacity retention rate at 25°C is determined as follows: At 25°C, charge the battery at a constant current of 1C to 4.55V, then charge at a constant voltage of 4.55V until the current drops to 0.05C. Discharge the battery at a constant current of 1C to 2.5V to obtain the first-cycle discharge capacity (Cd1). Repeat this cycle for 100 cycles, and the discharge capacity after n cycles is calculated as (Cdn). Capacity retention rate = discharge capacity after n cycles / discharge capacity in the first cycle.

Claims

1. A separation film comprising: First basement membrane; a second base film, the melting point of the second base film being lower than the melting point of the first base film; The porosity of the first base film is denoted as P1, and the porosity of the second base film is denoted as P2, then 1.02≤P1 / P2≤3.

2. The isolation film according to claim 1, wherein: 1.05≤P1 / P2≤2.

5.

3. The isolation film according to claim 1 or 2, wherein: The porosity of the first base film is 30%-90%, and can be 35%-85%; and / or The porosity of the second base film is 30%-70%, and can be optionally 35%-45%.

4. The isolation film according to any one of claims 1 to 3, wherein: The ratio of the average pore size of the first base film to the average pore size of the second base film is 0.05-80, and can be 0.2-40; Optionally, the average pore size of the first base film is greater than the average pore size of the second base film; Optionally, the average pore size of the first base film is 100nm-4000nm, optionally 100nm-2000nm; Optionally, the average pore size of the second base film is 50nm-2000nm, optionally 50nm-500nm.

5. The isolation film according to any one of claims 1 to 4, wherein: The transverse tensile strength of the first base film is less than the longitudinal tensile strength of the first base film; the ratio of the transverse tensile strength of the first base film to the longitudinal tensile strength of the first base film is 0.2-0.8, and can be optionally 0.3-0.

6.

6. The isolation film according to any one of claims 1 to 5, wherein: The transverse tensile strength of the second base film is less than the longitudinal tensile strength of the second base film; optionally, the ratio of the transverse tensile strength of the second base film to the longitudinal tensile strength of the second base film is 0.45-0.9, and can be optionally 0.6-0.

8.

7. The isolation film according to any one of claims 1 to 6, wherein: The transverse tensile strength of the first base film is less than the transverse tensile strength of the second base film; and / or, The longitudinal tensile strength of the first base film is smaller than the longitudinal tensile strength of the second base film.

8. The separator according to any one of claims 1 to 7, wherein: The isolation film satisfies at least one of the following (1)-(4): (1) The transverse tensile strength of the first base film is 150-900 Kgf / cm 2 , optional 200-750Kgf / cm 2 ; (2) The longitudinal tensile strength of the first base film is 800-2500 Kgf / cm 2 , optional 1100-1900Kgf / cm 2 ; (3) The transverse tensile strength of the second base film is 1500-3600 Kgf / cm 2 , optional 1800-3300Kgf / cm 2 ; (4) The longitudinal tensile strength of the second base film is 1900-4000 Kgf / cm 2 , optional 2000-3500Kgf / cm 2 .

9. The isolation film according to any one of claims 1 to 8, wherein: The ratio of the thickness of the first base film to the thickness of the second base film is greater than or equal to 1.02, and can be selected to be 1.2-3.

0.

10. The isolation film according to any one of claims 1 to 9, wherein: The thickness of the first base film is 2 μm-12 μm, and can be 3 μm-6 μm; and / or The thickness of the second base film is 2 μm-12 μm, and can be 3 μm-5 μm.

11. The isolation film according to any one of claims 1 to 10, wherein: The ratio of the melting point of the first base film to the melting point of the second base film is greater than or equal to 1.05 and less than or equal to 3.0, and can be greater than or equal to 1.1 and less than or equal to 2.

5.

12. The isolation film according to any one of claims 1 to 11, wherein: The melting point of the first base film is 160° C.-360° C., and can be 180° C.-350° C.; and / or The melting point of the second base film is 120°C-280°C, and can be optionally 130°C-265°C.

13. The isolation film according to any one of claims 1 to 12, wherein: The first base film and the second base film are each independently selected from at least one of polyolefins and their derivatives, halogenated polyolefins and their derivatives, polyethers and their derivatives, polyetheretherketones and their derivatives, polyesters and their derivatives, polyimides and their derivatives, polyvinyl alcohols and their derivatives, polytetrafluoroethylene and their derivatives, polyvinyl fluoride and their derivatives, polyvinylidene fluoride and their derivatives, and polyethylene terephthalate and its derivatives.

14. The isolation film according to any one of claims 1 to 13, wherein: Also includes: an adhesive layer, disposed between the first base film and the second base film, the adhesive layer comprising a binder; Optionally, the bonding layer includes a binder and a filler.

15. The isolation film according to claim 14, wherein: The binder includes one or more of polyacrylate, polyacrylic acid, polytetrafluoroethylene, polyvinylidene fluoride, vinylidene fluoride-trichloroethylene copolymer, polyvinyl pyrrolidone, polyvinyl acetate, ethylene-vinyl acetate copolymer, polyethylene oxide, polyarylate, carboxymethyl cellulose, hydroxypropyl cellulose, regenerated cellulose, cellulose acetate, cellulose acetate propionate, cellulose acetate butyrate, polyacrylonitrile, polyvinyl alcohol, polyethylene, polypropylene, starch, and cyanoethyl pullulan.

16. The isolation film according to claim 14 or 15, wherein: The filler includes at least one of inorganic particles, organic particles, and organic-metal framework materials.

17. The isolation film according to any one of claims 14 to 16, wherein: The thickness of the adhesive layer is greater than or equal to 0.3 μm, and can be optionally 0.5-2 μm.

18. The isolation film according to any one of claims 1 to 17, wherein: The air permeability of the isolation film is 200s / 100cc-400s / 100cc, and can be optionally 250s / 100cc-320s / 100cc; and / or The porosity of the isolation film is 25%-80%, and can be optionally 35%-55%.

19. A method for preparing an isolation film, comprising: Providing a first base film and a second base film, wherein the melting point of the second base film is lower than the melting point of the first base film, the porosity of the first base film is recorded as P1, the porosity of the second base film is recorded as P2, and 1.02≤P1 / P2≤3; The first base film and the second base film are compounded to obtain the isolation film.

20. The method for preparing an isolation film according to claim 19, wherein: Also includes: Providing a bonding layer slurry, wherein the bonding layer slurry includes a binder; The adhesive layer slurry is arranged on the first base film and / or the second base film to form an adhesive layer, and after compounding, the adhesive layer is located between the first base film and the second base film; Optionally, the bonding layer slurry further comprises a filler; optionally, the filler comprises inorganic particles, At least one of organic particles and organic-metal framework materials. 21 . A secondary battery, comprising the separator according to any one of claims 1 to 20, or the separator prepared by the preparation method according to claim 19 or 20.

22. The secondary battery according to claim 21, wherein The secondary battery further includes a positive electrode sheet and a negative electrode sheet, and the second base film faces the negative electrode sheet.

23. An electrical device comprising the secondary battery according to claim 21 or 22.